Exploring Students' Perceptions of their Experiences in a Social Justice Living–Learning Community. Issue 2 (15th March 2019) - Jessup-Anger, Jody; Armstrong, Megan; Kerrick, Elizabeth; Siddiqui, Noreen
Abstract : This qualitative study explored students' perceptions of their experience in a social justice living–learning community throughout their time in the community and one year after participation. Findings illustrated students (1) developed a broader conception of social justice and greater awareness of social justice issues in the community, (2) increased their capacity for social justice and civic engagement, and, (3) established enduring values, which included appreciation for community and increased capacity for social connection.